Pelatihan Manajemen Sekolah Berbasis eSchool untuk Meningkatkan Kompetensi Kepala Sekolah TK ABA Se-Kota Mataram - Maemunah, Maemunah; Dewi, Citra Ayu; Sakban, Abdul (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service aims to improve the competence of the principal of ABA Kindergarten in the city of Mataram. The method of implementing this service used training and mentoring with stages of preparation, implementation, evaluation and follow-up plans. The evaluation instrument for this activity used a survey questionnaire related to the knowledge and skills of school principals in eschool-based school management. The data analysis technique was the percentage distribution of the principal's competence before and after the training. The results of this community service showed that the principal's competence in eschool-based school management has increased after being given training. Thus, it can be concluded that eschool-based school management can improve the competence of ABA kindergarten principals in the city of Mataram.